Sodobna zakonska ureditev visokega šolstva - Bohinc, Rado (Teorija in praksa, 2017)
The aim of the article is to examine the gap between the reality and both the recommendations and guidelines of various international (Bologna and EU) documents regarding the questions of university autonomy, and to propose solutions to ensure its greater autonomy within the national higher education system. We first present the international higher education community's guidelines and recommendations concerning various aspects of university autonomy. Based on this review, we identify questions that relate to the constitutional and legal position of the university as an institution in Slovenia. This is followed by an analysis of the legal framework, the legal status of public entities, and the university-state relationship while also presenting disparities from the constitutionally established autonomy of universities from different perspectives. The research findings reveal that the current university system as regulated by the Higher Education Act is inadequate. We therefore argue that truly establishing the constitutionally guaranteed autonomous university requires the higher education legislation to be amended in terms of modernising and improving the Slovenian higher education system (preparation and adoption of a particular university law).
Keywords: Autonomy; Avtonomija; Higher education; Legislation; University; Univerza; Visoko šolstvo; Zakonodaja